Therapeutic exploitation of IPSE, a urogenital parasite-derived host modulatory protein, for chemotherapy-induced hemorrhagic cystitis - Mbanefo, Evaristus C.; Le, Loc; Pennington, Luke F.; Odegaard, Justin I.; Jardetzky, Theodore S.; Alouffi, Abdulaziz; Falcone, Franco H.; Hsieh, Michael H. (Federation of American Society of Experimental Biology, 2018)
Chemotherapy-induced hemorrhagic cystitis (CHC) can be difficult to manage. Prior work suggests IL-4 alleviates ifosfamide-induced hemorrhagic cystitis (IHC), but systemically administered IL-4 causes significant side effects. We hypothesized that the Schistosoma haematobium homolog of Interleukin-4-inducing principle from Schistosoma mansoni Eggs (H-IPSE), would reduce IHC and associated bladder pathology. IPSE binds IgE on basophils and mast cells, triggering IL-4 secretion by these cells. IPSE is also an “infiltrin”, translocating into the host nucleus to modulate gene transcription. Mice were administered IL-4, H-IPSE protein or its nuclear localization sequence (NLS) mutant with or without neutralizing anti-IL-4 antibody, or MESNA, followed by ifosfamide. Bladder tissue damage and hemoglobin content were measured. Spontaneous and evoked pain, urinary frequency and gene expression were assessed. Pain behaviors were interpreted in a blinded fashion. One dose of H-IPSE was superior to MESNA and IL-4 in suppressing bladder hemorrhage in an IL-4-and NLS-dependent fashion, and comparable to MESNA in dampening ifosfamide-triggered pain behaviors in an NLS-dependent manner. H-IPSE also accelerated urothelial repair following IHC. Our work represents the first therapeutic exploitation of a uropathogen-derived host modulatory molecule in a clinically relevant bladder disease model, and indicates that IPSE may be an alternative to MESNA for mitigating CHC.